An experimental study on the properties changing in recyclable fiber‐reinforced 3D printing. Issue 10 (17th June 2022) - Wei, Wei; Chen, Ling; Zhang, Lijing; Yang, Jinxiu; Yao, Yuan; Zhang, Heng
Abstract: Continuous fiber‐reinforced composites 3D printing can significantly improve strength but make materialize recycling more difficult. This study explores the feasibility of recycling and remanufacturing in practical applications by simulating the change in mechanical properties during outdoor aging of continuous aramid fiber‐reinforced 3D printed parts. First, a Fermat's Spiral based globally continuous path was used to fabricate recyclable fiber‐reinforced prints. Then, the continuous aramid fiber‐reinforced PLA (CF/PLA) composites were recycled from the printed parts and re‐impregnated in the subsequent production. Finally, the CF/PLA composite specimens were exposed to UV irradiation and moisture cycling in an aging test chamber, and the aging process of the whole experiment lasted for 516 h. It was found that for the first recycled and remanufactured specimens, the tensile strength was 204 MPa, which was higher than that of the originally printed specimens (196 MPa), and the flexural strength and modulus were 159 MPa and 6.4 GPa, higher than those of original specimens, which were 141 MPa and 5.6 GPa, an increase of 12.77% and 14.29%, respectively. For the specimens aged 172, 344, and 516 h, the tensile strength increased by 4.32%, 3.60%, and 17.36%, respectively after recycling and remanufacturing. The reduction rate of the tensile strength of the remanufactured specimens was 15.3% lower than that of the raw materials in the aging process. Our experiments estimated the change in properties of remanufactured specimens from recycled fiber‐reinforced materials after natural aging, demonstrating the feasibility of the manufacturing process for recycled fiber‐reinforced materials in practical applications. Abstract :